2019
DOI: 10.3389/fimmu.2019.01019
|View full text |Cite
|
Sign up to set email alerts
|

IRF1 Maintains Optimal Constitutive Expression of Antiviral Genes and Regulates the Early Antiviral Response

Abstract: Viral defense at mucosal sites depends on interferons (IFN) and IFN stimulated genes (ISGs), either of which may be constitutively expressed to maintain an “antiviral state” (AVS). However, the mechanisms that govern the AVS are poorly defined. Using a BEAS-2B respiratory epithelial cell line deficient in IRF1, we demonstrate higher susceptibility to infection with vesicular stomatitis virus (VSV) and influenza virus. IRF1-mediated restriction of VSV is IFN-independent, as blockade of types I and III IFNs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 53 publications
7
79
0
1
Order By: Relevance
“…IRF1 and IRF2 are antagonistic to each other (55,56,58), but help maintain a fine balance in expression of both MX1 and TMPRSS2. Loss of IRF2 recognition site, due to rs35074065-delC variant, leads to increased IRF1 mediated expression of MX1 (53). Recent analysis by Human Lung Cell Atlas group identified that ACE2 and TMPRSS2 are interferon regulated and ACE2+ TMPRSS2+ Single cells that express both ACE2 and TMPRSS2, also express innate immunity associated genes like MX1, IDO1, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IRF1 and IRF2 are antagonistic to each other (55,56,58), but help maintain a fine balance in expression of both MX1 and TMPRSS2. Loss of IRF2 recognition site, due to rs35074065-delC variant, leads to increased IRF1 mediated expression of MX1 (53). Recent analysis by Human Lung Cell Atlas group identified that ACE2 and TMPRSS2 are interferon regulated and ACE2+ TMPRSS2+ Single cells that express both ACE2 and TMPRSS2, also express innate immunity associated genes like MX1, IDO1, etc.…”
Section: Discussionmentioning
confidence: 99%
“…We bioinformatically identified transcription factor binding sites around the rs35074065 locus. A recognition site for transcription factor IRF1 (Interferon Regulatory Factor 1), which is known to activate MX1 (53), was present in the sequences -containing the reference (C) and the variant (delC) alleles -around the rs35074065 eQTL. IRF1 is known to activate genes in response to viruses (54).…”
Section: The Clade Specific D614g Mutation Provides Advantage To A2a mentioning
confidence: 99%
“…Increased expression of CEBPD also elevates the expression of IL-6 (Hungness et al, 2002). IRF1 mediates both innate and adaptive responses to viral infection such as inducing apoptosis and restricting viral replication (Kanazawa et al, 2004;Kung et al, 2014;Nair et al, 2017;Panda et al, 2019). Both target genes are highly indicated in the immune related pathways found FIGURE 8 | Bar chart representing the number of genes indicated in each of the significant and specific immune-related pathways found using GO and GeneAnalytics.…”
Section: Discussionmentioning
confidence: 99%
“…They are responsible for the ongoing COVID-19 pandemic and the attendant significant morbidity and mortality (Gussow et al, 2020;Lucas et al, 2020). Bovine coronavirus (BCoV) is endemic worldwide and affects both wild and domesticated cattle (Saif, 2010), causing disease affecting the respiratory system and gastrointestinal tract, with pathogenesis ranging from mild to fatal (Underwood et al, 2015;Oma et al, 2016). BCoV has high mortality rates in calves, inducing wasting and flattening of the villi in the GI and a substantial cause of calf diarrhea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation